Immigration policy and institutional violence: Biopolitic analysis of the chilean case - Orrego Rivera, Cristián; Herrera Vergara, Constanza (Revista Némesis, 2021)
Through Michel Foucault’s concepts of biopower, biopolitics and governmentality, state’s sovereignty and the traditional conception of citizenship are analysed as the fundamental pillars of migration policy. The analysis of the policies adopted by President’s Sebastián Piñera current government, implemented during the first year of administration (March 2018 until March 2019), taking into consideration its scope, shape and effects, distinguishes between those based on selection and restriction criteria, obtaining as a result the make live and let die determined flows or groups of migrants. This analysis allows to identify the mechanisms of biopolitics used by the state’s administration, throughout which institutional violence is exercised upon population, meanwhile hygienist, productive or reproductive concerns are summoned.